Transforming Lecturer Identity: Exploring the Emotional and Professional Impact of Teaching on Novice Lecturers in Early Career Academia - Elihami Elihami; Muwafiq Ibrahim Mas’ud; Hadi Pajarianto; Ismail Ismail; Sri Rosmiana (Majesty Journal, 2025)
This study investigates the emotional and professional impacts of teaching on novice lecturers at Universitas Muhammadiyah Enrekang, focusing on the process of identity transformation. New lecturers face numerous emotional and professional challenges, including stress, role ambiguity, and feelings of isolation, particularly during the initial years of teaching. This research adopts a qualitative approach, using semi-structured interviews with 22 novice lecturers from various academic disciplines to gain insights into their experiences. The study found that institutional support, particularly mentorship from the Chair of the Department and peer collaboration, plays a crucial role in helping lecturers navigate these challenges and develop a professional identity. Although the institution provides some support, findings suggest that more structured mentorship and additional resources are necessary to better support novice lecturers. The study contributes to existing literature on the identity formation of novice lecturers, especially in non-Western academic settings, and highlights the need for tailored support strategies that address the specific challenges faced by new faculty members. These insights are valuable for improving institutional practices and enhancing the professional satisfaction and development of novice lecturers.